Apparent piezoelectric response from the bending of non-poled PVDF. (23rd May 2019) - Zhou, Yang; Liu, Jie; Hu, Xinping; Salem, David R.; Chu, Baojin
Abstract: By exploiting the flexoelectric effect, piezoelectric composites, in which none of the individual components is piezoelectric, can be designed. Here, the flexoelectric piezoelectric composite was designed and fabricated using polyvinylidene fluoride (PVDF). Although the flexoelectric response of PVDF is much lower than that of ferroelectric ceramics, which are normally utilized to fabricate the piezoelectric composites because of their high flexoelectric response, a relatively high apparent piezoelectric response (>11 pC N −1 ), is obtained in the polymer-based composite because of its low elastic modulus. Our results demonstrate that polymers can be used to fabricate composites with good piezoelectric response and mechanical reliability.